KONSEP DIRI FANS K-POP KOREABOO DI SURABAYA (Universitas Negeri Surabaya, 2023)
Korean culture and the spread of Kpop nowdays which has increasingly expanded to all corners of the world have resulted in an increasing number of fans from Korean culture and the Kpop genre itself. Among these Kpop fans, there are some of them who are koreaboo. The term koreaboo itself is a discourse that is often used for fans who are more fanatical. This research aims to find out how the self-concept of Koreaboo Kpop fans in Surabaya. This study uses the phenomenological method with data collection techniques in the form of interviews, which then the findings in the interviews are analyzed using the Self-Concept Theory expressed by George Herbert Mead. The results of this research indicate that Koreanboo Kpop fans in Surabaya in the process of forming self-concepts also go through three self-concept ideas put forward by Mead, namely: mind, self, society